The Genome of a Bacillus Isolate Causing Anthrax in Chimpanzees Combines Chromosomal Properties of B. cereus with B. anthracis Virulence Plasmids - Klee, Silke R.; Brzuszkiewicz, Elzbieta B.; Nattermann, Herbert; Brüggemann, Holger; Dupke, Susann; Wollherr, Antje; Franz, Tatjana; Pauli, Georg; Appel, Bernd; Liebl, Wolfgang; Couacy-Hymann, Emmanuel; Boesch, Christophe; et al. (PloS one, 2010)
Anthrax is a fatal disease caused by strains of Bacillus anthracis. Members of this monophyletic species are non motile and are all characterized by the presence of four prophages and a nonsense mutation in the plcR regulator gene. Here we report the complete genome sequence of a Bacillus strain isolated from a chimpanzee that had died with clinical symptoms of anthrax. Unlike classic B. anthracis, this strain was motile and lacked the four prohages and the nonsense mutation. Four replicons were identified, a chromosome and three plasmids. Comparative genome analysis revealed that the chromosome resembles those of non-B. anthracis members of the Bacillus cereus group, whereas two plasmids were identical to the anthrax virulence plasmids pXO1 and pXO2. The function of the newly discovered third plasmid with a length of 14 kbp is unknown. A detailed comparison of genomic loci encoding key features confirmed a higher similarity to B. thuringiensis serovar konkukian strain 97-27 and B. cereus E33L than to B. anthracis strains. For the first time we describe the sequence of an anthrax causing bacterium possessing both anthrax plasmids that apparently does not belong to the monophyletic group of all so far known B. anthracis strains and that differs in important diagnostic features. The data suggest that this bacterium has evolved from a B. cereus strain independently from the classic B. anthracis strains and established a B. anthracis lifestyle. Therefore we suggest to designate this isolate as "B. cereus variety (var.) anthracis".